2008
DOI: 10.1074/jbc.m706136200
|View full text |Cite
|
Sign up to set email alerts
|

The Association of GSK3β with E2F1 Facilitates Nerve Growth Factor-induced Neural Cell Differentiation

Abstract: It is widely acknowledged that E2F1 and GSK3␤ are both involved in the process of cell differentiation. However, the relationship between E2F1 and GSK3␤ in cell differentiation has yet to be discovered. Here, we provide evidence that in the differentiation of PC12 cells induced by nerve growth factor (NGF), GSK3␤ was increased at both the mRNA and protein levels, whereas E2F1 at these two levels was decreased. Both wild-type GSK3␤ and its kinase-defective mutant GSK3␤ KM can inhibit E2F1 by promoting its ubiqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…As previously described (Zhou et al, 2008), PC12 cells grown on collagen coated glass coverslips were washed twice with PBS, fixed with 4% paraformaldehyde in PBS for 15 min, permeabilized with 0.1% Triton X-100 for 10 min, and blocked with 3% BSA in PBS for 60 min. The cells were then incubated with primary antibodies diluted in TBST (20 mmol/L Tris-HCl, pH 7.6, 137 mmol/L NaCl, 0.1% Tween 20) for 3 h and washed twice with p PBS and incubated with fluorescein isothiocyanate (FITC) conjugated anti-mouse or antirabbit antibodies for an additional 40 min.…”
Section: Immunofluorescencementioning
confidence: 99%
See 2 more Smart Citations
“…As previously described (Zhou et al, 2008), PC12 cells grown on collagen coated glass coverslips were washed twice with PBS, fixed with 4% paraformaldehyde in PBS for 15 min, permeabilized with 0.1% Triton X-100 for 10 min, and blocked with 3% BSA in PBS for 60 min. The cells were then incubated with primary antibodies diluted in TBST (20 mmol/L Tris-HCl, pH 7.6, 137 mmol/L NaCl, 0.1% Tween 20) for 3 h and washed twice with p PBS and incubated with fluorescein isothiocyanate (FITC) conjugated anti-mouse or antirabbit antibodies for an additional 40 min.…”
Section: Immunofluorescencementioning
confidence: 99%
“…As previously described (Zhang et al, 2004(Zhang et al, , 2006Zhou et al, 2008;Zhang et al, 2011), cells were lysed with 1 mL of lysis buffer (20 mmol/L Tris-HCl, pH 7.4, 2 mmol/L EDTA, 25 mmol/L NaF, 1% Triton X-100) supplemented with protease inhibitors (Sigma) for 30 min at 4°C. After centrifugation at 12,000 g for 15 min, the lysates were immunoprecipitated with specific antibody and protein ASepharose (Zymed Laboratories Inc.) for 3 h at 4°C.…”
Section: Immunoprecipitation and Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation
“…E2F1 can control cell proliferation and differentiation. Overexpression of E2F1 significantly inhibits neuronal differentiation [26] . We have found that Omi is increased and E2F1 is decreased in differentiated N2a cells ( Figure 4A).…”
Section: Wwwchinapharcom Ma Q Et Almentioning
confidence: 99%
“…The expression of E2F1 is irreversibly downregulated during the differentiation of C2C12 myocytes [25] . Additionally, the association of GSK3β with E2F1 facilitates nerve growth factor-induced PC12 cell differentiation, and overexpression of E2F1 inhibits neurite outgrowth [26] .…”
Section: Introductionmentioning
confidence: 99%